State Aid for Green Technologies in the European Union: Limitations and Risks (Polish Yearbook of International Law, 2024)
This article analyzes the recently adopted European Union State aid rules designed to facilitate the implementation of “green” technologies. This initiative is in line with European objectives to combat climate change and transition to an emission-free economy. By contextualizing State aid rules within the broader regulatory policy landscape, the author aims to assess the inherent limitations of these tools. Based on this evaluation, the article attempts to determine if and to what extent EU State aid law can be successfully utilized to promote environmental objectives.The analysis begins with an overview of the State aid toolbox and its role in regulatory policies, situated on a spectrum between incentive-based and obligation-based approaches. Subsequently, it delves into the evaluation of potential consequences, encompassing risks such as the deepening disparities between wealthier and poorer Member States, inadequate safeguards against offshoring in pursuit of lenient environmental norms, and the peril of fostering subsidy dependence.